Thirty Years After Bill 101: A Contemporary Perspective on Attitudes Towards English and French in Montreal - Kircher, Ruth (Canadian Journal of Applied Linguistics, 2014)
Abstract This paper presents a 2007 study that was conducted amongst 147 young anglophone, francophone and allophone Montrealers in order to shed light on their attitudes towards English and French in terms of status and solidarity. The study made use of both a questionnaire and a matched-guise experiment. The findings indicate that while a certain amount of status was attributed to French, most likely as a result of language policy and planning measures such as Bill 101, significantly more status was attributed to English—most likely a result of the utilitarian value that the language holds as the global lingua franca. Regarding the solidarity dimension, it appears that while the respondents recognised the social desirability of having an affective attachment to the French language, at a more private level, they held more positive attitudes towards English. These can tentatively be explained in terms of the respondents’ social identity. Résumé L’article ci-dessous présente une recherche menée en 2007 parmi 147 étudiants montréalais (anglophones, francophones et allophones) qui eut pour objectif d’examiner leurs attitudes envers l’anglais comparé au français en terme de statut et de solidarité. Un questionnaire et une étude des faux-couples furent utilisés comme méthodes de recherche. Les résultats indiquent qu’un certain statut est attribué au français, ce qui est probablement une conséquence des lois langagières comme la Loi 101. Néanmoins, un statut plus important est attribué à l’anglais, ce qui est probablement une conséquence de sa valeur utilitaire comme lingua franca globale. En ce qui concerne la dimension de la solidarité, bien que les jeunes montréalais semblent conscients de l’importance sociale de se sentir attachés à la langue française, lorsque l’on considère un aspect plus personnel, ils tendent à manifester des attitudes plus positives envers l’anglais. Ces attitudes plus positives envers l’anglais peuvent être expliquées comme résultats de différentes identités sociales.